Sighted Assumptions to Blind Imaginings: De-Centring Vision as Unexpected Dramaturgy - Bulmer, Alex (Performance Matters, 2025)
In this article, Canadian-born Blind theatre artist Alex Bulmer identifies the significant events that shaped and informed her dramaturgical practice over multiple decades. Alex reflects on (1) the access infrastructure within the UK that enabled her to develop deeper dramaturgical thinking; (2) a more profound and connected approach to dramaturgy that Alex discovered and developed as a series of “Blind Imaginings” practices; and (3) how this practice continues to de-centre visuality in performance.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)Alex Bulmer is a Blind theatre artist who was born in Canada. In this article, she talks about the events that have shaped how she makes plays. Alex thinks about:The ways the UK supports access. This support let her think deeply about how plays mean and feel. The ways of making plays mean and feel that Alex developed. Alex calls these “Blind Imaginings.” The plays and creative projects the Blind Imaginings were developed for. How Blind Imaginings can create plays and art where seeing is not as important to meaning making as hearing, touching, and remembering.